Usefulnes of intracavitary recording in the ablation of nodal reentry tachycardia - Roberto Zayas Molina; Jesús Castro Hevia; Margarita Dorantes Sánchez; Frank Tornés; Francisco Dorticós Balea (ECIMED, 2014)
The results obtained in 3 patient carriers of nodal reentry tachycardia that underwent ablation with radiofrecuency were analized. With the applications of energy on the lower third of Koch's triangle, an exit site of the slow patway conduction, the fast patway was destroyed and a temporary auriculoventricular block was produced. 2 of the patients had a proonged P-R interval and the 3 of them had no retrograde conduction. The recording of the coronary simus during the applications allowed to define enlargements of the ventriculoauricular interval during the coupled rhythm that showed the injury of the retrograde fast pathway and the conduction by the slow pathway. It is concluded that the prolongation of the ventriculoauricular interval appearing with the coupled rhythm dirung the applications of radiofrequency may be a marker that defines the of the fast patway nodal conduction. the intracardiac recording (caronary sinus) is indispensable to make this diagnosis.